Emplacement History of the Miocene Zebín Tuff Cone (Czech Republic) Revealed From Ground Geophysics, Anisotropy of Magnetic Susceptibility, Paleomagnetic, and 40Ar/39Ar Geochronology Data. (18th October 2018) - Petronis, Michael; Valenta, Jan; Rapprich, Vladislav; Lindline, Jennifer; Heizler, Matthew; van Wyk de Vries, Benjamin; Shields, Sarah; Balek, Jan; Fojtíková, Lucia; Tábořík, Petr
Abstract: The Zebín Volcano, Czech Republic, is a quarried tuff cone that offers the opportunity to understand emplacement processes responsible for magma transport through a pyroclastic cone and magmatic processes involved in its development. A high‐resolution ground magnetometry survey, electrical resistivity tomography, and refraction seismic were conducted to supplement field mapping of the size, shape, and inner structure of the volcanic system. The Zebín Volcano yields normal polarity rocks, and the cone is underlain by a complex and branching magma feeder system with several diverging dikes. Samples were collected at 24 sites from feeder dikes and the main conduit for anisotropy of magnetic susceptibility and paleomagnetic analysis. Anisotropy of magnetic susceptibility results yield inferred magma flow directions indicating subhorizontal magma flow toward and away from the axial conduit as well as both upward and downward flow. Paleomagnetic data from all sites are normal polarity with statistically distinct remanence directions between some sites that indicate that significant time passed or deformation occurred during the growth of this volcanic system. 40 Ar/ 39 Ar isochron ages of groundmass provide emplacement ages of 18.38 ± 0.03 and 18.45 ± 0.03 Ma, whereas a weighted mean date of 18.52 ± 0.03 Ma for hornblende provides an eruption age. We argue that the Zebín Volcano evolved from a polyphase feeding system and through a complex feeder network. This detailed study shows that many monogenetic volcanoes deserve highly detailed study, as their subtleties can provide insight into broader crustal and magmatic environment during magmatism. Key Points: The data from Zebín Volcano reveal that multiple magma conduits were emplaced and the volcano erupted over a protracted period of time Paleomagnetic data show evidence for subvolcanic deformation associated with the growth of the volcano Geophysical data image the subsurface geometry of the volcanic magma feeder system